STUDI MINAT PENGGUNAAN QUICK RESPONSE INDONESIA STANDARD (QRIS) BAGI UMKM DI KOTA PONTIANAK - Rianti Ardana Reswari; Cesy Iola Kariza (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2023)
The utilization of recent technology for MSME players is a crucial step for building business resilience. The initial purpose of this research is to grasp the effect of the model expansion of Unified Theory of Technology Use Acceptance (UTAUT) and user trust in adopting digital payment system known as Quick Response Indonesia Standard (QRIS) particularly on MSMEs actor located in Pontianak. The aim of research is to examine the MSMEs behavioural intention in adapting the QRIS payment system. The research methodology employed is quantitative research. Primary data is the result from obtaining the data through answered multiple-choice questionnaire filled by the respondents. Purposive sampling technique is selected to meet the research objectives by determine the respondents’ characteristics which is MSMEs actor that aware of QRIS payment system mechanism however remain not utilize it. The research model will be calculated using Warp PLS 7.0 as statistical Structural Equation Model (SEM) analysis tools. It was found that MSME actors were not influenced by social influence in generating interest in using the QRIS payment system in business processes.